Application of entransy-dissipation-based thermal resistance for performance optimization of spiral-wound heat exchanger. (January 2018) - Wang, Simin; Jian, Guanping; Wang, Jiarui; Sun, Lijuan; Wen, Jian
Highlights: The effects of structural parameters on thermal resistance of entransy dissipations of SWHEs are studied. All the geometrical parameters are negatively correlated with R ff . The MOGA optimization of SWHE was carried out based on different types of objective functions. For optimization of SWHEs, the objective functions based on entransy theory are better. Abstract: The effects of geometrical parameters on thermal resistance based on entransy dissipation caused by heat transfer ( R ht ) and fluid friction ( R ff ) of spiral-wound heat exchanger (SWHE) were studied by numerical method. The simulation results show that all geometrical parameters (spiral angle, external diameter, layer pitch, tube pitch) are negatively correlated with R ff because of flow pattern transition caused by the variation of geometrical parameters and the changing of effective flow area which would cause the decrease of entransy dissipation related to fluid friction. For the entransy dissipation due to the heat transfer, the increase of layer pitch are positive to it while both the tube pitch and external tube diameter are negative to R ht, and with the increase of the spiral angle, the R ht decrease at first and then increase. What is more, the MOGA optimization of SWHE was carried out based on different types of objective functions. Compared with the traditional objective functions (minimize Δ P and maximize K ), R ff and R ht obtained from minimizing the entransy-dissipation-based thermal resistance reduce by an average of 90.51% and 34.13%, respectively. Compared with original structure, the comprehensive performance evaluation factor ( Nu/f 1/3 ) of traditional optimal results is improved by an average of 41.02%, while that of optimal structures obtained from entransy theory is strengthened by an average of 76.64%. The results demonstrate that the objective functions of minimizing the entransy-dissipation-based thermal resistance are better than that of traditional objective functions for optimization of spiral wound heat exchanger.